Analisis Dari Allah Yang Memenuhui Janjinya Kepada Kita Umatnya Dan Negeri Yang Sudah Di Janjikan Tuhan (Yosua 21:43 -45) - Titin Wulandari Malau; Netty Tesa Yolanika (International Forum of Researchers and Lecturers, 2024)
In the context of everyday life, this shows the importance of stability, continuity and blessings in human life, which they believe come from God. And in Christianity, every person has the right to interpret the contents of the Bible, thus he is called an interpreter. Interpreting the Bible is not immediately aims to change/rationalize the original text of the Bible, but aims to find a different theology by looking at it from a different perspective so as to produce a new meaning. In interpreting Bible verses/texts, we must not interpret it out of context, and God also gave the Israelites peace and there were also those who took issue with settling the division of land between the tribes of Israel after they entered the land of Canaan. This chapter records how God was faithful in fulfilling His promise to the Israelites by giving them the promised land in Canaan. In this context, there is no specific problem, but rather an important achievement in the history of Israel under Joshua's leadership after they emerged from wandering in the wilderness. And this also reflects an achievement and settlement of the Israelite society, allowing them to live more stably, cultivate land, and building community in the promised land.